2011
DOI: 10.5326/jaaha-ms-5710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of a Posttraumatic Intrahepatic Biloma in a Dog

Abstract: A 9 mo old male mixed-breed dog was presented with a history of chronic vomiting and fever after undergoing a cholecystectomy for the management of traumatic cystic duct rupture associated with biliary effusion 10 days before referral. A 6 cm × 6 cm intrahepatic bile collection, a biloma, was diagnosed on abdominal ultrasound and fine-needle aspiration. The biloma was treated with percutaneous catheter drainage under ultrasonographic guidance. Two years after aspiration, the dog continued to do well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In this case, the ultrasonographic examination revealed several anechoic lesions in the liver and near the gall bladder. 1 The ultrasonography was useful in demonstrating the lesions. However, aspiration and analysis of the fluid were necessary to confirm the diagnosis of biloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the ultrasonographic examination revealed several anechoic lesions in the liver and near the gall bladder. 1 The ultrasonography was useful in demonstrating the lesions. However, aspiration and analysis of the fluid were necessary to confirm the diagnosis of biloma.…”
Section: Discussionmentioning
confidence: 99%
“…Bilomas are well-demarcated, encapsulated or not, extra or intrahepatic collections of bile that result secondary to rupture of the biliary tree, which can be spontaneous, traumatic or iatrogenic following surgery or interventional procedures. 1 It is a rare condition, and little information is available in veterinary medicine. 2 The objective of this report is to describe a case of traumatic bilomas associated with previous polytrauma due to a dog bite.…”
Section: Introductionmentioning
confidence: 99%
“…A few reports have been available on bilomas in veterinary medicine, including three dogs and one cat with biloma. In one dog, biloma developed after surgical treatment of intrahepatic portosystemic shunt ( 7 ), whereas in the other dog, biloma was associated with trauma (hit by a car) ( 10 ). Moreover, biloma in a cat developed after open liver biopsy ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common therapeutic approach in human patients with bilomas is percutaneous drainage ( 3 , 4 ). Studies in veterinary medicine involving two dogs with bilomas who underwent percutaneous drainage showed that both dogs had good outcomes without such a surgical approach for biloma ( 8 , 10 ). However, the current dog with biloma had been managed with supportive therapy and cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation